Theoretical bases of formation of commercialization mechanism of innovative technologies - Плахотнік, Олена Олександрівна (Technology audit and production reserves, 2015)
Common approaches to the definition of «technology commercialization» and «technology transfer» are discussed in the article. As a result of analysis definitions it was concluded that the concept of «technology commercialization» and «technology transfer» must be regarded as autonomous processes of innovation, as they can be held independently of each other. Analysis of the problems and features of formation of modern mechanism of commercialization of innovation technologies was conducted, the main components of the commercialization mechanism of innovative technologies are considered and especially their manifestations in Ukraine are determined. As a result of research was made the conclusion that the lack of a holistic methodology for studying the processes of commercialization of innovative technologies, the underestimation of the role and importance of commercialization in the formation of an innovative economy does not contribute to the effective technical-economic development of Ukraine on the basis of production using advanced technologies.